The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2017
DOI: 10.3748/wjg.v23.i18.3262
|View full text |Cite
|
Sign up to set email alerts
|

Artificial liver support in pigs with acetaminophen-induced acute liver failure

Abstract: AIMTo establish a reversible porcine model of acute liver failure (ALF) and treat it with an artificial liver system.METHODSSixteen pigs weighing 30-35 kg were chosen and administered with acetaminophen (APAP) to induce ALF. ALF pigs were then randomly assigned to either an experimental group (n = 11), in which a treatment procedure was performed, or a control group (n = 5). Treatment was started 20 h after APAP administration and continued for 8 h. Clinical manifestations of all animals, including liver and k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…Current literature reports of drugs that can induce ALF include those on D-gal, acetaminophen (APAP), and carbon tetrachloride, to name a few[ 12 - 14 ]. Yu et al[ 22 ] reported on the pharmacokinetics, drug metabolism, and hepatic toxicity of APAP in cynomolgus monkeys and found significant tolerance to APAP; therefore, APAP is not suitable to create a cynomolgus monkey model to study related hepatic injury.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Current literature reports of drugs that can induce ALF include those on D-gal, acetaminophen (APAP), and carbon tetrachloride, to name a few[ 12 - 14 ]. Yu et al[ 22 ] reported on the pharmacokinetics, drug metabolism, and hepatic toxicity of APAP in cynomolgus monkeys and found significant tolerance to APAP; therefore, APAP is not suitable to create a cynomolgus monkey model to study related hepatic injury.…”
Section: Discussionmentioning
confidence: 99%
“…There are current literature reports of many drugs that have been used to induce animal models of ALF[ 5 , 12 - 14 ]. D-galactosamine (D-gal) is a disruptor of uridine triphosphate of hepatocytes, causing diffuse hepatic necrosis and an inflammatory response, similar to the pathological changes of clinical viral hepatitis[ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Yi Gao’s team established a BAL system consisting of a perfusion bioreactor and CL‐1 human hepatocytes line to treat D‐galactosamine (D‐GALN)‐induced ALF monkeys and acetaminophen (APAP)‐induced ALF animal models . The results supported a positive effect on prolonging survival time of ALF pigs.…”
Section: Progress On Bioartificial Liver (Bal)mentioning
confidence: 95%
“…Pigs are a valuable translational biomedical tool, particularly for modeling human liver disease. Robust porcine models of cirrhosis [1][2][3][4] , non-alcoholic steatohepatitis 5,6 , hepatocellular carcinoma 7,8 , diabetes [9][10][11] , hereditary tyrosinemia type 1 [12][13][14][15] and acute liver failure 16,17 have all been reported and mimic many clinical manifestations of the human disease. Biomedical imaging can be used in conjunction with these porcine models in many ways.…”
Section: Introductionmentioning
confidence: 99%